Nipple Sensation and Nipple–Areolar Complex Outcomes After Oncoplastic Breast Surgery - Austin Olano, MD; John Chou, BS; Emma Lampropoulos, MD, MPH; Jeffrey Aalberg, MD, MPH; Michael Jonczyk, MD, MS; Salvatore Nardello, DO, MBS; Sarah Persing, MD, MPH; Abhishek Chatterjee, MD, MBA (Plastic and Reconstructive Surgery, Global Open)
Background:. Oncoplastic breast surgery (OBS) is a form of breast conservation surgery that integrates cancer removal with the reconstruction of the breast and immediate contralateral symmetry surgery followed by adjuvant radiation. This study aimed to identify differences in nipple–areolar complex (NAC) outcomes by comparing the oncological breast (which also receives adjuvant radiation) to the contralateral breast following OBS. Methods:. Interviews containing validated nipple-focused questions were conducted on 28 patients (encompassing 56 breasts) who had undergone OBS with immediate contralateral symmetry surgery followed by adjuvant radiation. Outcomes were ranked on Likert scales. A Wilcoxon signed-rank test was used to analyze the results for differences in rankings between the oncological breast and the contralateral symmetry breast. Results:. There were no statistically significant differences in patient satisfaction with nipple height or NAC shape when comparing breasts having undergone oncological resection versus symmetry surgery. A majority of patients reported being satisfied with the look of the NAC on the oncological breast. There was less reported nipple sensation on the oncological breast compared with the symmetry breast; however, there was no statistically significant difference in patient satisfaction with nipple sensation. Conclusions:. Nipple–areolar outcomes following OBS and adjuvant radiation are favorable in terms of patient sensation and appearance particularly when compared with the contralateral breast undergoing symmetry reduction surgery. These findings can enhance the preoperative counseling of patients in the breast cancer surgical decision-making process.